Preferensi Visual Pengguna Usia Paruh Baya Pada Live Streaming E-Commerce - Harahap, Widiya Lestari; Olivia, Yaya; Sari, Dely Indah (Visualita Jurnal Online Desain Komunikasi Visual, 2026)
The development of live streaming e-commerce has driven changes in consumer behavior across age groups, including middle-aged users (40–60 years old) who possess significant economic potential but have different visual preferences compared to younger generations. This study aims to identify visual preferences and formulate user-centered design recommendations. The method employed is User-Centered Design (UCD), consisting of context analysis, user needs identification, design development, and evaluation. Data were collected through in-depth interviews and pre-test–post-test questionnaires, and analyzed using the Paired Samples T-Test. The results indicate that effective design elements include a simple layout, larger typography, calm color schemes with contrasting accents, enlarged icons, and clearer pricing and promotional information. The implementation of user-centered visual elements has been shown to improve comfort and positive visual perception among middle-aged users. Statistical analysis shows a significant increase in visual preference scores from 28.60 to 41.50 (t = -9.254; p < 0.001) after design implementation.